Cover, Content, and Editorial Note from Borneo J Pharm Vol. 4 No. 4 November 2021 - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published at November 2021. Starting from this volume, Borneo J Pharm increases the frequency of publishing four times a year. This change aims to improve circulation of the best articles published by Borneo J Pharm. This edition contains ten articles consisting of Pharmacognosy-Phytochemistry, Analytical Pharmacy-Medicinal Chemistry, Microbiology Pharmacy, Natural Product Development, and Clinical-Community Pharmacy. This edition includes writings from six countries including India, Indonesia, Nigeria, Pakistan, Sri Lanka, and Turkey. The authors come from several institutions, including the University of Jaffna, Shri Gopichand College of Pharmacy, Government College University Faisalabad, Galgotias University, University of Delhi, Universitas Lambung Mangkurat, Universitas Sembilanbelas November Kolaka, Sathyabama Institute of Science and Technology, Ege Üniversitesi, Universitas Sam Ratulangi, Prathima Institute of Medical Sciences, Dr. NTR University of Health Sciences, Ganapathy Degree College, National Agency of Drug and Food Control of Republic of Indonesia, National Agency of Drug and Food Control of Republic of Indonesia in Gorontalo, National Institute for Pharmaceutical Research and Development, Universitas Jenderal Achmad Yani, and Ibrahim Adjie Health Center. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. We hope that all parties, especially the contributors, could re-participate for the publication in the next edition on February 2022. Wassalamu’alaikum Wr. Wb.